Functional Outcome of Congruent ARC Laterjet Procedure in Off Track Lesions of Shoulder with Recurrent Anterior Shoulder Instability (Journal of Pakistan Orthopaedic Association, 2024)
Objective: To evaluate the functional outcomes of the congruent arc Latarjet procedure in off-track lesions with recurrent shoulder instability.Methods: This retrospective study included 25 patients who underwent surgical treatment for recurrent anterior shoulder instability at Liaquat National Hospital between January 2017 and January 2021. The patients met the inclusion criteria of having recurrent shoulder instability with glenoid bone loss exceeding 20% and an off-track lesion. The Congruent Arc Latarjet procedure was performed on all patients. The functional outcomes of the patients were evaluated using the visual analogue score (VAS), Rowe score, and range of motion before surgery and at 1, 6, 12, and 24 months postoperatively.Results: A total of 25 patients were evaluated post-operatively for 24 months. VAS and ROWE score improved from 7.4 ± 0.91 and 20.80 ± 2.46 preoperatively to 1.48 ± 0.58 and 95.76 ± 1.83 respectively (p < 0.05) at 24 months postoperatively. Based on ROWE score, 23 (92%) had an excellent outcome and 2 (8%) had a good outcome 24 months after the surgery. Range of motion also improved significantly from forward flexion improving to 160.1 ± 7.01 from 72.84 ± 3.98 and external rotation to 45.16 ± 2.89 from 9.60 ± 2.34, at 24 months postoperatively.Conclusion: The congruent arc Laterjet procedure is an effective technique for the treatment of recurrent shoulder instability with off-track lesions as it produced excellent outcome in restoring shoulder function and stability.